Adsorption Kinetics Studies of Polymeric Nanocomposite Coagulants. Issue 3 (March 2013) - Uzunsakal, Seher; Zeytinci, Serhat; Uyanık, Ömer L.; Uyanık, Nurseli
The aim of this study is to investigate the adsorption characteristics of dicyandiamide-formaldehyde resin (DCD-F) nanocomposites. For this purpose, 2%, 4%, and 8% unmodified layered silicate clay (Na-Montmorillonite) containing DCD-F nanocomposites (DCD-F- MMT) were prepared. The synthesized samples were structurally defined by XRD, SEM-EDX, and TGA characterizations. The adsorption performance of nanocomposites was tested by using two anionic dyes. Adsorption capacities of pure resin and three nanocomposites were followed against time and the nanocomposite containing 8% Na-MMT (DCD-F-MMT8%) was found to have the highest equilibrium adsorption capacity (qe ). Therefore, the effects of dye concentration, pH, and temperature on qe were investigated using DCD-F-MMT8%. The kinetic and thermodynamic parameters of adsorption were obtained based on the experimental data.